2023
DOI: 10.3390/s23042357
|View full text |Cite
|
Sign up to set email alerts
|

H-Shaped Radial Phononic Crystal for High-Quality Factor on Lamb Wave Resonators

Abstract: In this paper, a novel H-shaped radial phononic crystal (H-RPC) structure is proposed to suppress the anchor loss of a Lamb wave resonator (LWR), which has an ultra-high frequency (UHF) and ultra-wideband gap characteristics. Compared to previous studies on phononic crystal (PC) structures aimed at suppressing anchor loss, the radial phononic crystal (RPC) structure is more suitable for suppressing the anchor loss of the LWR. By using the finite element method, through the research and analysis of the complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…The structures investigated here stem from the physical mechanism of local resonance, which have an edge on traditional Bragg scatter types [ 12 , 13 , 14 , 15 ]. Typically, the BGs of Bragg scatter types generally have high frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…The structures investigated here stem from the physical mechanism of local resonance, which have an edge on traditional Bragg scatter types [ 12 , 13 , 14 , 15 ]. Typically, the BGs of Bragg scatter types generally have high frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Phononic crystal [ 1 ] is an artificial periodic composite material/structure with an elastic wave band gap that has attracted extensive interest from scholars at home and abroad in recent years. Due to the elastic band gap characteristics [ 2 , 3 , 4 , 5 ] of the phononic crystal structure, vibration will be difficult to propagate in the corresponding band gap, so there are many potential applications in vibration and noise reduction [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ] that can be widely used in ships, aircraft, and other engineering fields. In existing studies, Bragg scattering [ 15 ] and local resonance [ 16 ] are the main mechanisms of band gap formation, between which locally resonant phononic crystals can generate low-frequency band gaps.…”
Section: Introductionmentioning
confidence: 99%
“…Radial phononic crystals (RPCs) are cyclic structures periodically arranged along the radial direction based on cylindrical coordinate system, and they have complete band-gap characteristics [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Torrent et al studied the propagation characteristics of body waves in RPCs and found that the propagation of body waves in specific frequency bands were prohibited, and they verified the band-gap characteristics [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The RPCs designed by the above researchers have excellently achieved isolating acoustic waves. In the field of MEMS resonators, He et al proposed an H-shaped RPC structure for a Lamb-wave resonator based on a cylindrical coordinate system [ 28 ], which generated a band gap and improved the Q of the resonator. Since the studied structure was a single material, this caused some strength damage to the resonator at the anchor point when etching the substrate, which resulted in poor stability of the structure.…”
Section: Introductionmentioning
confidence: 99%